2002
DOI: 10.1097/00004836-200204000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myeloid Leukemia Presenting as Obstructive Jaundice

Abstract: A 36-year-old man presented with abdominal pain and jaundice. Ultrasound examination of the abdomen showed dilatation of the intrahepatic bile ducts and a normal common bile duct. No calculi were demonstrated. A computerized tomography scan did not show any masses. A peripheral blood smear was diagnostic of acute myeloid leukemia. After remission-inducing chemotherapy, there was a complete regression of the jaundice, which had not recurred at the 12-month follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…Liver parenchymal infiltration due to AML is rarely reported in the literature. The majority of cases presented with cholestasis and obstructive jaundice4; however, few case reports have described a transaminitis without evidence of cholestasis 5. Previously reported patients with this diagnosis have been treated with cytarabine and anthracycline at the time of diagnosis but most patients only experience remission for a short period of time 4.…”
Section: Discussionmentioning
confidence: 99%
“…Liver parenchymal infiltration due to AML is rarely reported in the literature. The majority of cases presented with cholestasis and obstructive jaundice4; however, few case reports have described a transaminitis without evidence of cholestasis 5. Previously reported patients with this diagnosis have been treated with cytarabine and anthracycline at the time of diagnosis but most patients only experience remission for a short period of time 4.…”
Section: Discussionmentioning
confidence: 99%
“…19 Goor, Yoav et all, published a paper on acute myeloid leukemia presenting as obstructive jaundice. 20 We strongly believe that the elevated ALP and gamma GGT are due to infiltration of leukemic cells and obstruction of biliary tracts. Our study showed relationship between elevated ALP and GGT with high bone marrow blasts.…”
Section: Discussionmentioning
confidence: 98%
“…Obstructive jaundice arising from merely leukemic infiltrate of the bile ducts has been rarely reported to show a favorable response to systemic therapy and mandate further local intervention. 10,11 Goor et al reported a patient who presented with obstructive jaundice and a rapid rise in bilirubin level. 11 Prompt chemotherapy without temporary drainage procedures resolved presumptive biliary leukemic infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Goor et al reported a patient who presented with obstructive jaundice and a rapid rise in bilirubin level. 11 Prompt chemotherapy without temporary drainage procedures resolved presumptive biliary leukemic infiltration. Mano et al, in the report on a patient who presented with jaundice in whom computed tomography disclosed thickening of the common bile duct, noted possible institution of chemotherapy after placement of endoscopic nasobiliary drainage.…”
Section: Discussionmentioning
confidence: 99%